Teleconnections between tropical-extratropical oceans and the daily intensity of extreme rainfall over Argentina - Robledo, F.A. (2013)
A Singular value decomposition (SVD) analysis was performed jointly on the daily intensity of extreme rainfall (DIER) over Argentina and the sea surface temperature (SST) of all the oceans from 17.5°N to 90°S in order to identify the large-scale variability of the SSTs related to extreme rainfall, in the period 1962-2005. The main objective of the article is to objectively recognize regions of the tropical and subtropical oceans that could be related with the extreme rainfall over Argentina. Spring is the season that is best represented by the first mode, accounting for up to 45% of the covariance between the DIER and SST. The first SVD mode of spring, summer and autumn presents a pattern of SST relating to the El Niño-Southern Oscillations (ENSO) phenomena with an enhanced DIER in different zones of centre and east of Argentina. In the second SVD mode of spring and summer, the SST patterns show cold conditions in the tropical and subtropical Atlantic and near Indonesia with an enhancement of the DIER in the centre and east of Argentina. These modes show a significant decadal variability. In the third SVD mode of spring and summer, the SST patterns present warm and cold conditions in the Indian Ocean and the centre and western Pacific Ocean (PO) with decreased rainfall in the northern and eastern portion of Argentina, respectively. This mode shows a significant period of temporal variability of around 14 years. The third mode of autumn presents warm conditions in the tropical Atlantic and the southwest PO with a low DIER in the centre and east of Argentina. This mode also presents temporal variability of around 14 years. The correlation between each mode derived from analysis of SVD and climate indices related with SST were computed. © 2012 Royal Meteorological Society.